Accountable Governance in the Procurement of Goods and Services in Teluk Bintuni Regency - Hellyn Kristiono; Hasniati Hasniati; Muh. Akmal Ibrahim (Journal Social Civilecial, 2025)
This study aims to understand the application of accountable governance principles in goods and services procurement practices in Teluk Bintuni Regency through the aspects of Publicity, Supervision, Audit, Responsibility, and Sanction using a qualitative approach. The research focused on local government institutions directly involved in the procurement process. Informants were selected purposively based on their roles and involvement. The results of this study indicateSeveral findings, the first of which is that in Teluk Bintuni Regency, publicity has been institutionalized through an electronic system, but has not yet achieved substantive transparency. Furthermore, other findings indicate that although procurement supervision in Teluk Bintuni Regency has been designed in a layered manner, its implementation is still fragmented and tends to be administrative. Likewise, audit practices in Teluk Bintuni Regency still tend to be oriented towards administrative compliance. In terms of the division of roles, it has been understood and implemented administratively, but responsibility is still interpreted only as fulfilling procedures, not as a substantive commitment to quality and the public interest. And finally, the results of the study also show the weak implementation of sanctions in Teluk Bintuni Regency, reflecting what Mulgan (2000) calls